2015
DOI: 10.4314/gmj.v49i1.11
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus Negative Woman Transfused With Rhesus Positive Blood: Subsequent Normal Pregnancy Without Anti D Production

Abstract: Clinicians sometimes are confronted with the challenge of transfusing haemorrhaging Rhesus (Rh) D negative patients with Rh D positive blood to save their lives. There are concerns about alloimmunization and future haemolytic disease of the newborn in women of the reproductive age. Another fear is transfusion reaction if they receive another Rh D positive blood in future. We present a 32-year-old Rh D negative woman, who had postpartum haemorrhage in her first pregnancy and was transfused with Rh D positive bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
1
Order By: Relevance
“… 29 30 Individuals who are Rh negative produce anti-D if they are transfused with blood which is Rh positive. 31 The proportion of blood donors in the present study with Rh negative was 4.7% still low when compared with 2% which was reported in Tanzania from a study which had a sample size of 1845 blood donors which is quite insignificant when compared with 65 535 blood donors in the current study. Studies have shown that the incidence of Rh negative may stand up to 17% globally.…”
Section: Discussioncontrasting
confidence: 70%
“… 29 30 Individuals who are Rh negative produce anti-D if they are transfused with blood which is Rh positive. 31 The proportion of blood donors in the present study with Rh negative was 4.7% still low when compared with 2% which was reported in Tanzania from a study which had a sample size of 1845 blood donors which is quite insignificant when compared with 65 535 blood donors in the current study. Studies have shown that the incidence of Rh negative may stand up to 17% globally.…”
Section: Discussioncontrasting
confidence: 70%
“…Solving the age-long controversies on anti-HBc inclusion or exclusion in HBV screening for blood transfusion/organ transplant requires multiple strategies. Firstly, optimal blood donor selection methods that promote 100% voluntary non-remunerated blood donation according to vision 2020 set by the World Health Organization [43,44] and reverse the current trend of 30%, 60% and 10% replacement, commercial and voluntary blood donations respectively [45] should be adopted in Nigeria.…”
Section: Optimal Donor Selection Methodsmentioning
confidence: 99%
“…Also, for those quite remote from the term, conservative management may be instituted after the initial surgical intervention. 26 Despite the low rate of successful post-SHiP pregnancy continuation, patients should be made aware of the possibility of miscarriage, recurrence of SHiP during the index and subsequent pregnancy. 11 Also, the possibility of an emergency surgical intervention should be discussed with the patient.…”
Section: Management Strategiesmentioning
confidence: 99%